Metadiscurso e metáfora na publicidade multimodal do Banco Itaú: Um enfoque da Linguística Sistêmico-Funcional - Crucciani, Maria Helena Mitson (2021)
With the increasing use of technology in communication, we are increasingly surrounded by texts with complex, dense, multilevel forms of meaning. Recent research in the field of multimodal studies aims to understand how meanings are made within and through semiotic resources often unheard of in multimodal artifacts and events. The phenomenon of multimodality moves from the center of gravity of linguistic concerns to the concerns of semiotics. In this context, advertising, in terms of discourse genre, seems to be better represented as a continuum of functions of the text floating between "inform" and "manipulate", in which persuasion acts on the underlay of the text. Thus, based on the view of multimodality as a social and communicative engagement, involving cultural diversity, it becomes important, in persuasive terms, the notion of metadiscourse, which refers to the organization of discourse as well as to the author's positioning in relation to the content of the message or spectator. At its side, the importance of the relationship between metaphor and conceptual metonymy is being increasingly recognized and studied by cognitive linguists, as research has consistently proven that conceptual metaphors always involve a degree of perspective, when certain traits are highlighted while others remain obscured, to the taste of the author's will. In this process, the metaphor depends on conceptual metonymy, which, thanks to its indicial character, is a cognitive process that evokes a frame, allowing the addressed to infer the implicit content of the message, giving meaning to apparently anomalous and disconnected statements. The objective of this master's thesis is the critical examination of multimodal advertising by Banco Itaú, focusing on metadiscourse and the conceptual metaphor/metonymy relationship, supporting the theoretical-methodological proposal of Systemic-Functional Linguistics. The research shows that multimodal advertising moves from the center of gravity of linguistic concerns to the concerns of semiotics, and critical analysis is not enough to examine metadiscourse in verbal mode only, because the persuasion that Banco Itaú exerts on the public depends on the conjugation of the verb-visual. However, to understand the message contained therein and understand how it reaches the reader, it is necessary to support conceptual metonymy, which allows to make by contiguity the relationship between the choices made in the text of advertising with the interlocutor's frame. These choices – the metonymy – add up, revealing in the discourse the underlying metaphor of the text